Principle of accounting - Nik Ibrahim, Nik Haslina; Mazali, Manizah; Mohd. Noor, Rohana; Hussain, Husnamaria; Abdul Rahman, Noredah; Mohd. Daud, Norhazni (Cengage Learning Asia Pte. Ltd., 2015)
The first edition of Principles of Accounting is written for readers who have no basic accounting. The book covers the principles in financial accounting as well as introductory management accounting Hence, the reader will not only learn about accounting basics mainly for record keeping, but will also learn how to manage a business using accounting information